Fostering Resilience in Educational Institutions: Strategies for Sustainable Growth - Jain, Rachna; Sharma, Shikha (JOURNAL OF INDIAN EDUCATION, 2026)
In today’s dynamic and unpredictable environment, educational institutes face a myriad of challenges that can disrupt their operations and impact their ability to fulfil their core mission of educating students. From natural disasters and pandemics to economic downturns and social unrest, the need for resilience in educational settings has never been more evident. This paper explores the multifaceted nature of resilience in educational institutes, examining its theoretical foundations, practical implications and strategies for implementation. Drawing upon a review of relevant literature and case studies, the paper highlights the importance of adaptability, resourcefulness, collaboration and emotional intelligence in fostering resilience. It also discusses the role of leadership, organisational culture, community engagement and external support systems in enhancing resilience within educational institutes. By offering insights into the complexities of resilience and providing actionable strategies for building resilience in educational settings, this paper aims to empower educators, administrators and policymakers to navigate challenges effectively, and ensure the continuity of learning and achievement for all students.